2019
DOI: 10.2337/db18-1055
|View full text |Cite
|
Sign up to set email alerts
|

Osteoprotegerin Promotes Liver Steatosis by Targeting the ERK–PPAR-γ–CD36 Pathway

Abstract: Previous cross-sectional studies have established that circulating osteoprotegerin (OPG) levels are associated with nonalcoholic fatty liver disease (NAFLD). However, the role of OPG in metabolic diseases, such as diabetes and NAFLD, is still unclear. In the current study, we demonstrated that hepatic OPG expression was downregulated in NAFLD individuals and in obese mice. OPG deficiency decreased lipid accumulation and expression of CD36 and peroxisome proliferator–activated receptor-γ (PPAR-γ) in the livers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
54
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(60 citation statements)
references
References 53 publications
6
54
0
Order By: Relevance
“…Insulin resistance (IR) is the pathophysiological basis of metabolic diseases, such as type 2 diabetes mellitus (T2DM), metabolic syndrome (MetS) and nonalcoholic fatty liver disease (NAFLD) [1][2][3][4]. Increased IR in T2DM patients, obesity and MetS individuals is a high-risk factor for cardiovascular disease (CVD) [5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Insulin resistance (IR) is the pathophysiological basis of metabolic diseases, such as type 2 diabetes mellitus (T2DM), metabolic syndrome (MetS) and nonalcoholic fatty liver disease (NAFLD) [1][2][3][4]. Increased IR in T2DM patients, obesity and MetS individuals is a high-risk factor for cardiovascular disease (CVD) [5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Peroxisome proliferator-activated receptor gamma (PPARγ), a number of the nuclear hormone receptor family, exerts a crucial role in mediating inflammatory diseases (e.g., colitis [14], liver steatosis [15], and rheumatoid arthritis [16]) and inflammatory and neuropathic pain development [17].…”
Section: Introductionmentioning
confidence: 99%
“…More importantly, CD36 is also involved in regulating chronic metabolic inflammation by activating the JNK pathway (Kennedy et al, 2011). A recent study suggested that osteoprotegerin (OPG) can regulate CD36 transcription through the ERK-PPARγ pathway, thus promoting hepatic steatosis (Zhang et al, 2019a).…”
Section: Introductionmentioning
confidence: 99%